2021
DOI: 10.1186/s12891-021-03945-y
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized trial of workplace ergonomics and neck-specific exercise versus ergonomics and health promotion for office workers to manage neck pain – a secondary outcome analysis

Abstract: Background Neck pain is prevalent among office workers. This study evaluated the impact of an ergonomic and exercise training (EET) intervention and an ergonomic and health promotion (EHP) intervention on neck pain intensity among the All Workers and a subgroup of Neck Pain cases at baseline. Methods A 12-month cluster-randomized trial was conducted in 14 public and private organisations. Office workers aged ≥18 years working ≥30 h per week (n = 74… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…According to Kotz and colleagues [ 45 ], the most important disadvantage is that an intervention is implemented in all clusters, whereas it has not yet proven to be effective. However, in our case several components of our intervention already proved to be effective in other studies [ 12 , 13 , 17 , 21 , 29 ]. Hence, a stepped-wedge design is superior both scientifically (more data) and ethically as has been pointed out by Mdege and colleagues [ 46 ].…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…According to Kotz and colleagues [ 45 ], the most important disadvantage is that an intervention is implemented in all clusters, whereas it has not yet proven to be effective. However, in our case several components of our intervention already proved to be effective in other studies [ 12 , 13 , 17 , 21 , 29 ]. Hence, a stepped-wedge design is superior both scientifically (more data) and ethically as has been pointed out by Mdege and colleagues [ 46 ].…”
Section: Methodsmentioning
confidence: 49%
“…This is particularly an advantage from an ethical point of view, given that the intervention does more good than harm. Since previous research showed that individual components of our multi-component intervention were effective in reducing neck pain [ 12 , 13 , 21 ], the choice of the design seemed more appropriate compared to other study designs such as the classic cluster RCT. Detailed information can be found in the trial profile (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…While we believe that the reduction in neck cases was likely due to the exercise intervention, it is possible that factors not assessed also contributed to this finding. Nonetheless, we are confident in these results as adherence to the intervention on completion remained consistent for the control group while reducing for the exercise group 23. Other limitations include the use of self-reported outcomes and no evaluation on other potential confounders such as smoking habits.…”
Section: Discussionmentioning
confidence: 79%
“…Written informed consent was obtained from participants before data collection. The study protocol,21 and the results of the primary and secondary outcome have been published 22 23. The Consolidated Standards of Reporting Trials extension for cluster trials was observed for reporting 24.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation